ENDOPHYTIC BACTERIA ASSOCIATED WITH SUGARCANE AND ITS POTENTIAL TO SUPPRESS SPORISORIUM SCITAMINEUM, THE CAUSAL FUNGAL PATHOGEN OF SMUT DISEASE - Shadia Taghian; Afaf El-Meneisy; A. Esh; N. Abdel-Ghaffar (Arab Universities Journal of Agricultural Sciences, 2019)
Bacterial endophytic ubiquitously colonize the internal tissues of the plant. The purpose of this study was to isolate and identify the endophytic bacteria from sugarcane stalks which have antagonistic activity against Sporisorium scitamineum, the causal pathogen of sugarcane smut disease, and to study their activity to produce some secondary metabolites i.e. enzymes and growth-promoters.  Sugarcane samples were collected from five governorates in Upper-Egypt namely, Giza, Beni-Suef, Sohag, Qena, and Luxor. A total of 240 isolates of endophytic bacteria were isolated from 160 samples of healthy sugarcane stalks (variety GT-54-9). Isolated endophytes were screened for its antagonistic activity against S. scitamineum, in vitro, using dual culture method. Only, 62 isolates showed different degrees of antagonistic activity. Ten isolates of endophytic bacteria were selected to study their potential to produce enzymes (chitinase, β 1,3 glucanase, phenylalanine ammonia lyase) and growth-promoters (siderophores, indole acetic acid (IAA), salicylic acid (SA)). These isolates were pre-identified using the morphological and physiological properties according to Bergy's manual as Pseudomonas sp., Serratia sp., Enterobacteria sp., Herbaspirillium sp., Gluconacetobacter sp. Anabaenopsis sp. and Azospirillumsp. All endophetic bacteria produced β 1,3gluconase and indole acetic acid (IAA), while Pseudomonas sp. produced salicylic acid and phenylalanine ammonia lyase, Ana baenopsis sp. produced phenylalanine ammonia lyase, Gluconacetobacter sp. produced chitinase and Herbaspirillium sp. produced siderophore. Meanwhile, isolates of Anabaenopsis sp. and Pseudomonas sp. were the most effective to produce β 1,3glucanase and indole acetic acid compared with other entophytic bacteria.